Pengaruh Talent Management dan Keterlibatan Karyawan terhadap Daya Saing Perusahaan Hotel Sangga Buana - Alam, Fajar Nur; Wiludu, Bertha Mei; Muhammad Faiz Syauqy; Granit Agustina (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of Talent Management and Employee Engagement on the Company's Competitiveness at Hotel Sangga Buana. The research method used a quantitative approach with an associative design. Data were collected through questionnaires distributed to 47 employees and analyzed using multiple linear regression with the help of SPSS version 26. The results showed that Talent Management and Employee Engagement have a positive and significant effect on the Company's Competitiveness, with a simultaneous contribution of 52.3%. These findings indicate that effective talent management and high employee engagement are key factors in enhancing a company's competitiveness in the hotel industry.